Colloidal Nanospheres of Amorphous Selenium: Facile Synthesis, Size Control, and Optical Properties. Issue 6 (29th April 2021) - Cheng, Haoyan; Zhou, Shan; Xie, Minghao; Gilroy, Kyle D.; Zhu, Zhihong; Xia, Younan
Abstract: This article reports a facile method for the colloidal synthesis of nanospheres made of amorphous selenium ( ɑ‐ Se). The diameters of the nanospheres can be tightly controlled in the range of 45–157 nm by varying the reaction time and temperature, as well as the amount of the reducing agent. The average size of the nanospheres is measured using transmission electron microscopy and dynamic light scattering while their optical properties are characterized using UV‐vis spectroscopy. We also compute their UV‐vis spectra using the discrete dipole approximation (DDA) method and the calculated spectra are consistent with the experimental data based on the UV‐vis spectra and the particle sizes derived from electron microscopy. The data derived from DDA calculations provides a fitting curve for finely controlling the sizes of the ɑ‐ Se nanospheres by monitoring the UV‐vis spectra of the reaction solution at different stages of a synthesis. Abstract : Colloidal nanospheres made of amorphous selenium are synthesized using a simple and robust method, and their diameters can be readily tuned in the range of 45–157 nm with the assistance of UV‐vis spectroscopy.